Transmission performances of solitons in optical wired link - Amiri, I.S.; Ariannejad, M.M.; Ghasemi, M.; Ahmad, Harith (Elsevier, 2017)
Chaotic signal generation from microring resonators (MRRs) is presented. Two 1.5 μm Gaussians with spectral profile having powers of 600 mW are input into the system of MRRs. Using nonlinear conditions, the chaotic signals can be generated and propagated within the ring medium. Results show that the chaotic signals can be controlled and manipulated by using additional Gaussian input into the add port of the MRRs. A balance should be achieved between dispersion and nonlinear lengths when the propagating pulse is soliton. Chaotic output signals from the ring resonator can be converted to logic codes then inserted into an optical fiber transmission link which has a length of 180 km in order to perform the transmission performance. The transmitted signals in the form of spatial and temporal solitons can be detected at the end of the transmission link.